Assessment of bone mineral density should be considered earlier in perimenopausal women with vasomotor symptoms - YOLDEMİR, AHMET TEVFİK (WILEY, 2009)
Objective: To investigate the relationship between vasomotor symptoms (hot flashes) and osteopenia or osteoporosis in perimenopausal women. Method: In this cross-sectional study 79 perimenopausal women aged between 45 and 55 years and seen at the Gynecology or Menopause Outpatient Clinic of Marmara University School of Medicine were allotted to one of 2 groups according to the presence or absence of hot flashes. The groups were then compared for bone mineral density (BMD) of the lumbar vertebrae, as measured by dual energy X-ray absorptiometry. Results: The mean BMD measurement for vertebrae L2 to L4 was 0.32 +/- 0.19 for the group with no hot flashes and -0.53 +/- 0.21 for the group with hot flashes (P = 0.007). In the former, 6.1% of the women and in the latter, 32.6% of the women had a BMD value less than a 1.5 standard deviation from the mean (P = 0.005). Conclusion: Women with vasomotor symptoms are more prone to have osteopenia or osteoporosis. (C) 2009 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved
Keywords: Hot flashes; Osteopenia; Osteoporosis; Perimenopause; Vasomotor symptoms; RISK-FACTORS; HOT FLUSHES; MENOPAUSE; ESTROGENS; FRACTURE; MASS; AGE